Non-hormonal Clitoromegaly due to Clitoral Priapism Caused by Appendicitis/Appendectomy - Büşra Gürpınar Tosun; Ahsen Karagözlü Akgül; Eda Almus; Sadık Abidoğlu; Serap Turan; Abdullah Bereket; Tülay Güran (Galenos Yayincilik, 2023)
Clitoromegaly usually develops due to hyperandrogenism. There are a few cases of clitoromegaly described without clinical and biochemical hyperandrogenism. Clitoromegaly due to clitoral priapism and clitoral priapism after appendectomy have not been reported previously. A 7-year-old girl was referred for enlargement of the clitoris. She reported having a mild, pulsating clitoral pain starting three days after an appendectomy operation. Subsequently, painful swelling and an increase in the size of the clitoris was observed. Her growth and physical examination were otherwise normal. Causes of the clitoromegaly due to androgen excess were excluded after a comprehensive work-up. Color Doppler ultrasound revealed a high peak systolic velocity and resistance in the cavernosal artery, consistent with clitoral priapism. The clitoromegaly and associated symptoms improved significantly with oral pseudoephedrine and intracavernosal aspiration. This unique case illustrates that clitoral priapism is a rare, non-hormonal cause of clitoromegaly and may occur after appendectomy. Pseudoephedrine treatment is helpful in alleviating the symptoms.